THE EFFECT OF FINANCIAL PERFORMANCE, DIVIDEND POLICY, AND COMPANY SIZE ON PROFIT GROWTH IN PROPERTY & REAL ESTATE SECTOR COMPANIES LISTED ON THE IDX IN 2018-2022 - Muhammad Habibie; Siti Aisyah; Dwi Pertiwi Anggraini; Taufiq Risal; Irine Ika Wardhani; Ridho Gilang Adiko; Janit Putri Nainggolan (Adisam Publisher, 2025)
Profit growth is the company's ability to optimize the profits obtained and then compare them with the previous year's profits. Profit growth can indicate good operating conditions for a company, and if the economy is good it will influence profit growth. This research aims to determine the influence of Financial Performance, Dividend Policy, and Company Size on Profit Growth. This research is quantitative research with an associative approach. The population of this research is all property & real estate companies listed on the IDX. The sampling used in this research was purposive sampling with certain criteria so that 10 companies were obtained. This research uses multiple linear regression analysis tools equipped with classical assumption tests. The partial analysis results show that Financial Performance and Company Size have an effect on Profit Growth. Another thing is that Dividend Policy has no effect on profit growth. Simultaneous results show that Financial Performance, Dividend Policy and Company Size have an effect on Profit Growth.